The importance of Sambhasa (debate method) for increasing the self-confidence of the younger generation of Hindu in Bali - I Gusti Putu Gede Widiana; Anak Agung Raka Asmariani; I Made Sudarya, I Made Dirgantara Dwi Putra (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Introduction: Sambhasa is the art of debate and logic in India, equipped with a structured debating method. Hindu followers have three ways to resolve issues: first is Vada (discussion), second is Samvada (dialogue), and third is Tarka (Debate). Debate is a highly intellectual and refined skill aimed at elevating Hindus from various impure beliefs and thoughts that can be detrimental to Hindu Dharma. Methods: His article represents the outcome of a textual research study that examines the content, meaning, structure, and discourse of texts. The author analyzes both published texts that have undergone text criticism and unpublished texts or manuscripts. Finding: Debating becomes a fascinating discipline, inclusive of pramana, which involves seeking fundamental truths through four methods of observation: pratyaksa, anumana, upamana, and sabda, recognized by the Nyaya system as the four valid sources of knowledge. Debate is an engaging activity for the youth believed to boost confidence and shape positive character. Conclusion: However, a drawback lies in the dominance of participants who are confident and well-versed, overshadowing those who lack confidence and expertise in competitive debate.